2016
DOI: 10.1080/10942912.2016.1174939
|View full text |Cite
|
Sign up to set email alerts
|

Degradation kinetics of ascorbic acid in encapsulated spray-dried honey powder packaged in aluminium laminated polyethylene and high-density polyethylene

Abstract: To cite this article: Yogita Suhag & Vikas Nanda (2017) Degradation kinetics of ascorbic acid in encapsulated spray-dried honey powder packaged in aluminium laminated polyethylene and high-density polyethylene,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the IC 50 values of MNSO demonstrated a slight decrease after day 6 and reached 1.48 mg/mL on day 24. Similarly, Suhag et al [40] reported that encapsulated honey powder under prolonged storage resulted with initial increase of antioxidants and phenolic contents followed by decreased values through the storage duration. Overall, the antiradical activity of MNSO showed more stability than that of NSO during the accelerated storage period.…”
Section: Total Phenolic Contentmentioning
confidence: 91%
“…Furthermore, the IC 50 values of MNSO demonstrated a slight decrease after day 6 and reached 1.48 mg/mL on day 24. Similarly, Suhag et al [40] reported that encapsulated honey powder under prolonged storage resulted with initial increase of antioxidants and phenolic contents followed by decreased values through the storage duration. Overall, the antiradical activity of MNSO showed more stability than that of NSO during the accelerated storage period.…”
Section: Total Phenolic Contentmentioning
confidence: 91%
“…The present results revealed that at accelerated storage conditions lesser degradation of vitamin C occurs for powders in ALP package in contrast to HDPE package. The faster rate of degradation of vitamin C in HDPE packed powders is due to the higher oxygen transmission rate of HDPE pouches which accelerate the oxidation of vitamin C. Suhag and Nanda () reported similar results of vitamin C degradation in anola‐fortified honey powder. In this study regardless of the effect of type of packaging material (HDPE and ALP), vitamin C was found to be more stable in sprouted onion powder sample with less degradation due to its lower moisture content as compared to raw onion powder.…”
Section: Resultsmentioning
confidence: 90%
“…The decrease in equilibrium moisture content is due to the higher energy levels attained by water molecules at accelerated temperatures that drift away from the active water‐binding sites of the food (Palipane & Driscoll, ). This type of trend rendered the less hygroscopic nature of onion powders at higher temperature and less sorption of water at a particular water activity (Suhag & Nanda, ). From the sorption isotherms of onion powder samples (raw and sprouted), it has been found that both types of powders absorbed relatively less moisture at or below a w (<0.52) beyond which there was increase in water absorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations